Interlayer-Spacing-Modification of MoS2 via Inserted PANI with Fast Kinetics for Highly Reversible Aqueous Zinc-Ion Batteries - Shuang Fan; Yangyang Gong; Suliang Chen; Yingmeng Zhang (Micromachines, 2025)
Layered transition metal dichalcogenides (TMDs) have gained considerable attention as promising cathodes for aqueous zinc-ion batteries (AZIBs) because of their tunable interlayer architecture and rich active sites for Zn2+ storage. However, unmodified TMDs face significant challenges, including limited redox activity, sluggish kinetics, and insufficient structural stability during cycling. These limitations are primarily attributed to their narrow interlayer spacing, strong electrostatic interactions, the large ionic hydration radius, and their high binding energy of Zn2+ ions. To address these restrictions, an in situ organic polyaniline (PANI) intercalation strategy is proposed to construct molybdenum disulfide (MoS2)-based cathodes with extended layer spacing, thereby improving the zinc storage capabilities. The intercalation of PANI effectively enhances interplanar spacing of MoS2 from 0.63 nm to 0.98 nm, significantly facilitating rapid Zn2+ diffusion. Additionally, the π-conjugated electron structure introduced by PANI effectively shields the electrostatic interaction between Zn2+ ions and the MoS2 host, thereby promoting Zn2+ diffusion kinetics. Furthermore, PANI also serves as a structural stabilizer, maintaining the integrity of the MoS2 layers during Zn-ion insertion/extraction processes. Furthermore, the conductive conjugated PANI boosts the ionic and electronic conductivity of the electrodes. As expected, the PANI–MoS2 electrodes exhibit exceptional electrochemical performance, delivering a high specific capacity of 150.1 mA h g−1 at 0.1 A g−1 and retaining 113.3 mA h g−1 at 1 A g−1, with high capacity retention of 81.2% after 500 cycles. Ex situ characterization techniques confirm the efficient and reversible intercalation/deintercalation of Zn2+ ions within the PANI–MoS2 layers. This work supplies a rational interlayer engineering strategy to optimize the electrochemical performance of MoS2-based electrodes. By addressing the structural and kinetic limitations of TMDs, this approach offers new insights into the development of high-performance AZIBs for energy storage applications.